Integrating Local Culture-Based Learning Media in Multilingual Classrooms: An Analytical Study of Implementation and Educational Impact - Sudarsi, Elim Trika; Dan Mangoki’; Sri Wahyuni; Markus Deli Girik Allo; Tenri Ugi Irianto (Eduvelop: Journal of English Education and Development, 2025)
This study investigates the implementation of local culture-based learning media, specifically grounded in Toraja culture, within multilingual English classrooms at Universitas Kristen Indonesia Toraja. Using a qualitative case study approach, data were collected through classroom observations, document analysis, and in-depth interviews with English lecturers who actively integrate Torajan cultural elements—such as traditional narratives, rituals, and symbolism—into English language instruction. The findings reveal that such integration fosters culturally responsive instructional strategies, enhances student engagement, supports linguistic and intercultural competence, and affirms learners’ cultural identities. Lesson materials and teaching practices proved a successful bridging of content knowledge and cultural relevance, making English learning more accessible and meaningful. While the approach yielded clear pedagogical benefits, it also highlighted challenges including limited access to culturally adapted materials and the need for institutional support. The study concludes that with proper structural backing, the integration of local cultural media has transformative potential for inclusive, identity-affirming language education in multilingual contexts.